2018
DOI: 10.1371/journal.pone.0199218
|View full text |Cite
|
Sign up to set email alerts
|

Fall-risk-increasing drugs and falls requiring health care among older people with intellectual disability in comparison with the general population: A register study

Abstract: BackgroundFalls are the most common cause of injury for older people in the general population as well as among those with intellectual disability. There are many risk factors for falls, including a range of drugs which are considered to be fall-risk-increasing (FRIDs). The aim of the present study was to describe prescription patterns of FRIDs in itself as well as in relation to falls requiring health care among older people with intellectual disability and their age-peers in the general population. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…In summation, that prescription of psychotropics is common among people with ID has been reported before, both for the cohorts included in the present study [11, 17] and in other populations [23]. The present study shows that this excess is present even when restricting the study groups to those with diagnosis of anxiety and mood disorders, and that the underlying reason for prescription must be sought elsewhere than in the prevalence of these diagnoses.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…In summation, that prescription of psychotropics is common among people with ID has been reported before, both for the cohorts included in the present study [11, 17] and in other populations [23]. The present study shows that this excess is present even when restricting the study groups to those with diagnosis of anxiety and mood disorders, and that the underlying reason for prescription must be sought elsewhere than in the prevalence of these diagnoses.…”
Section: Discussionsupporting
confidence: 70%
“…We have previously found that older people with ID are more likely than their age-peers in the general population to be prescribed anxiolytics [11] and the GABA-agonist benzodiazepine [17]. At a first glance, this may be interpreted as a result of higher occurrence of psychiatric diagnoses in this group [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of suspected medication-related falls is about 41% [ 555 ] to 49% [ 556 ]. Increased risk of falls was documented in users of anxiolytics/hypnotics, opioids, sedatives, antihypertensives (especially alpha-blockers), antidepressants, antiparkinsonian medications, antiepileptics and antiarrhythmics [ 557 , 558 , 559 , 560 , 561 , 562 , 563 , 564 , 565 , 566 , 567 , 568 , 569 , 570 , 571 , 572 , 573 , 574 , 575 , 576 , 577 , 578 , 579 , 580 , 581 , 582 , 583 ]; polypharmacy is strongly associated with injurious falls and fractures [ 574 , 582 , 584 , 585 , 586 , 587 , 588 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…Previous studies regarding incidents among older people with ID have mainly focused on fall-related injuries Axmon, Sandberg, Ahlström, & Midlöv, 2018;, which is not surprising, as fractures are the most common cause of hospitalisation among diagnoses of injury, poisoning, and certain other consequences of external causes (Skorpen et al, 2016). Indeed, to the best of our knowledge, only one previous study has assessed poisonings and objects stuck in part of body (Finlayson, Morrison, Jackson, Mantry, & Cooper, 2010).…”
Section: Discussionmentioning
confidence: 99%